Professor surdo: desafios na construção de uma prática bilíngue - Hollosi, Marcio [UNIFESP] (2019)
The systematized study here analyzes a scenario pertaining to the Deaf teacher pedagogical practice in a bilingual school, aiming at analyzing the teaching processes (Didactics) used for teaching Deaf students, and , organizing spaces that allow the Deaf teachers involved, to reflect about their professional development as Deaf individuals and professionals, and about their practice (or performance) in the bilingual schools for Deaf students. Bibliographical research included didactics, bilingualism and bilingual education, as well as the teaching-learning process, the contribution of Educational Psychology, including the foundations of Vygotsky's Socio-Historical-Cultural approach (1924-1934) - basis for this dissertation thesis. This theoretical framework, together with the critical collaborative research (MAGALHÃES, 1990-2018), carried out with teachers through the filming of classes and reflective sessions, as well as semi-structured interviews between 2017 and 2018 in a private school for Deaf students, in the city of São Paulo, allowed us to identify some problems related to the didactics and teaching of the school subjects whose classes were observed. These problems were the target of discussions in the reflective sessions with the aim of constructing new practices (or, at least, of re-signifying the existing pracices). Data analysis was performed with the focus on the language and contents of the participants' speeches. In other words, we sought the lexical items that demonstrate the senses and meanings (VYGOTSKY, 1930) that each teacher has about the theme investigated in this paper (i.e., didactics and their action in the classroom with Deaf students). The results show that there is a lack of concern with didactic knowledge, rather there is a repetition of the means and practices by which the teachers were educated during their school years. This indicates a possible explanation for the problems encountered with the teaching-learning process, also indicating the urgency of reflections based on didactic (or pedagogical) issues pertaining to the Deaf teacher, especially in terms of the teaching of Libras and the teaching in Libras.